The ADDIE Model in Planning Indonesian Language and Literature Learning - Astuti, Astuti; Saleh, Andi Abdul Rahman; Haerul, Inglan Hadi; Dewi, Anita Candra (The Future of Education Journal, 2026)
This study aims to analyze the implementation of the ADDIE model in planning Indonesian Language and Literature instruction. The method employed is qualitative research with a literature review approach, drawing on books, journals, and relevant scientific articles as data sources. Data were collected through documentation analysis, while data analysis applied a descriptive qualitative approach. The findings indicate that the ADDIE model is a structured and systematic instructional design framework consisting of five stages: analysis, design, development, implementation, and evaluation. The implementation of this model in Indonesian Language and Literature instruction is considered effective because it can address students’ learning needs, improve the quality of instructional planning, and create more structured and meaningful learning processes. In addition, the ADDIE model is flexible and adaptable, allowing it to be applied in various learning contexts. Therefore, the ADDIE model can serve as an alternative approach for designing efficient, creative, and student-centered instruction aimed at improving students’ language skills.